PENGARUH PENGETAHUAN KEUANGAN DAN PENGALAMAN KEUANGAN TERHADAP PENGELOLAAN KEUANGAN DENGAN PENGENDALIAN DIRI SEBAGAI VARIABEL INTERVENING PADA GENERASI SANDWICH DI KOTA MEDAN - Qahfi Romula Siregar; Dedek Kurniawan Gultom; Lufriansyah Lufriansyah (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
This study aims to examine the effect of Financial Knowledge and Financial Experience on Financial Management, with Self-Control as an intervening variable among the Sandwich Generation in Medan City. The research employed an associative and quantitative approach. The population of this study consisted of all Sandwich Generation individuals in Medan City, whose total number was unknown. A sample of 100 respondents was determined using the Lemeshow formula. The research instruments included interviews, documentation studies, and questionnaires as data collection techniques. The data were analyzed using quantitative analysis with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach for path analysis. The results indicate that Financial Knowledge has a significant effect on Financial Management, Financial Experience has a significant effect on Financial Management, Financial Knowledge has a significant effect on Self-Control, Financial Experience has a significant effect on Self-Control, and Self-Control has a significant effect on Financial Management. Furthermore, Self-Control mediates the relationship between Financial Knowledge and Financial Management, as well as the relationship between Financial Experience and Financial Management. These findings suggest that improving financial knowledge and financial experience can enhance financial management directly and indirectly through increased self-control among the Sandwich Generation in Medan City. .